Preliminary ground based measurements of Aerosol Optical thickness over Udaipur (Rajasthan), India - Dave, Roshni; Aggarwal, Malini (My University, 2018)
We have carried out studies to understand the variability of Aerosol Optical Thickness (AOT) and precipitable water-vapour content (PWC) over Udaipur (24.58°N, 73.71°E), using hand-held microprocessor based MICROTOPS sun photometer-540 (1020 nm and 936 nm) from February, 2002 to March, 2004, excluding the rainy days (total of 156 days of clear-sky observations). We found that monthly AOT varied between 0.16 and 0.54 during the whole period and was higher in summer (mean value ~0.32) than the winter months (mean value ~0.19) with highest value in pre-monsoon month of June (0.54). The day-to-day variability of AOT is also higher in summer than winter months and is lowest during the post-monsoon months. We also found PWC to be maximum in monsoon month (July, ~3 cm) and minimum in December-February (~0.5 cm) winter months. A positive moderate correlation (0.45) between monthly AOT and PWC over the station during the study period is reported. This suggests that the production and loss of aerosol particles, which are hygroscopic in nature, are also associated with precipitable water-vapour content along with the other meterological factors.
Keywords: Aerosol; Climate; Precipitable water-vapour; Atmosphere